Trophic cascades and top-down control: found at sea - Surma, Szymon; Pakhomov, Evgeny A.; Pitcher, Tony J. (Frontiers in Ecology and Evolution, 2025)
This review investigates the current state of knowledge on trophic control and cascades in marine ecosystems. It critically examines claims that top-down control and trophic cascades are rarer in saltwater ecosystems than in their freshwater counterparts, that these phenomena are scarcer in the marine water column than in intertidal or benthic habitats, and that various abiotic and/or biotic factors explain the incidence of top-down control and trophic cascades in neritic and pelagic ecosystems. This review suggests that top-down control is more widespread in neritic and pelagic ecosystems than species-level trophic cascades, which in turn are more frequent than community-level cascades. The latter occur more often in marine benthic ecosystems than in their lacustrine and neritic counterparts and are least frequently found in pelagic ecosystems. These distinctions among ecosystem types likely derive from differences in the spatial dimensionality and scale of physical processes through their effects on nutrient availability and community composition. The incidence of community-level trophic cascades among neritic and pelagic ecosystems is inversely related to biodiversity and omnivory, which are in turn associated with temperature. Regional variability in benthic and neritic trophodynamics also results from differences in producer and consumer traits and food web structure. Fear of predators, rather than predation mortality itself, drives many marine trophic cascades and massive vertical migrations. Paradoxical and synergistic trophic interactions, as well as positive feedback loops derived from biological nutrient cycling, complicate the conventional dichotomy between top-down and bottom-up control. Finally, this review presents a set of ecological factors whose alternative states favor top-down or bottom-up control in marine ecosystems.